Recent advances on lignocellulosic bioresources and their valorization in biofuels production: Challenges and viability assessment - Srivastava, Neha; Singh, Rajeev; Singh, Pardeep; Ahmad, Irfan; Singh, Ravindra Pratap; Rai, Ashutosh Kumar; Asiri, Mohammed; Gupta, Vijai Kumar (Elsevier B.V., 2023)
Lignocellulosic biomass (LCB) waste materials are abundant in nature, and because of their high cellulose content, they rank among the most widely accessible and preferred feedstocks for the development of cost-effective biorefineries. The main obstacle to the long-term viability of this waste valorization at the pilot size, however, is the complexity of the structural composition of these wastes and the lack of a suitable bioprocess for their economical and efficient biotransformation. The current review investigates the potential for economically viable and environmentally friendly biotransformation of LCB wastes into cellulolytic enzymes and biofuels generation technologies. The review focuses on the efficient synthesis of enzymes and energy from LCB wastes through biotransformation. Based on the update progress, the information of the complexity constraint that currently exists in the LCB structure and the successful limitation surmounted have also been evaluated. To improve the overall bioprocess on a sustainable scale, other possible sustainable recommendations have also been proposed. Such LCB waste valorizations can contribute to the circular economy for sustainable future applications.
This paper published with affiliation IIT (BHU), Varanasi in open access mode.
Keywords: Biofuels; Biotransformation; Cellulolytic enzymes; Lignocellulosic biomass; Valorization